Republican lens: gender, visuality, and experience in the early Chinese periodical press - Judge, Joan (Asia, 2015)
"The early Republican (1911-1921) Chinese public looked, read, and interacted in profoundly different ways from its late imperial predecessor. While current scholarly has labeled the 1911 Revolution a virtual 'non-event' and the early Republic a political failure, the micro-historical view offered by the Chinese periodical press presents a much different perspective. Reversing orthodox academic practice, this book considers the realm of high politics as ephemeral and the institutions, associations, and practices of the reading and viewing public as the site of enduring and historical significance. The book centers on a selection of extraordinary photographic portraits taken from the periodical Funü shibao, one of the few journals to straddle the 1911 divide and remain in print through the early Republican period"--Provided by publisher
Includes bibliographical references and index
Keywords: China -- History -- Republic, 1912-1949; China -- Social conditions -- 1912-1949; China -- Social conditions -- 1912-1949 -- China -- History; Geschichte 1911-1921; Geschlechterrolle; Kommerzialisierung; Werbung; Frauenzeitschrift; China; Geschichte 1912-1949; Frauenbild; Frau; Zeitschrift